Implementation of the “SANTRI” moral movement as an effort to realise the Pancasila student profile - Wijayanti, Tutik; Suhardiyanto, Andi; Irawan, Hendri (Universitas Negeri Yogyakarta, 2025)
Education, apart from being an effort to transform knowledge, is expected to be able to transform good values in life. Currently, various moral problems in the world of education, especially among students in schools, are increasing, ranging from simple to complex issues. Strengthening the Pancasila Student Profile at school is seen as a strategic foundation to shape students with noble character aligned with the six dimensions of lifelong learners. One approach to instilling good character is through moral movements, where the method of habituation allows students to gradually apply values in their daily lives. Using a qualitative approach with data collected through observation, interviews, documentation, and literature review, this study explores how such movements operate in practice. Within this framework, the SANTRI moral movement emerges as a meaningful initiative that embodies politeness, independence, and excellence values that harmonise with the essence of the Pancasila Student Profile. When embedded into the school culture, these efforts subtly but powerfully influence students’ behaviour and mindset, offering a sustainable path toward cultivating strong moral foundations in education.